Impairment of the Akt pathway in transplanted Type 1 diabetic hearts is associated with post-transplant graft injury - Korkmaz-İçöz, Sevil; Li, Shiliang; Loganathan, Sivakkanan; Ruppert, Mihály; Brlecic, Paige; Veres, Gábor; Fleming, Thomas; Brune, Maik; Most, Patrick; Karck, Matthias; Szabó, Gábor (Interactive cardiovascular and thoracic surgery, 2018)
The use of ‘marginal’ hearts, such as from donors with diabetes mellitus (DM), could offer an opportunity to expand the donor pool in cardiac transplantation. Previous studies have shown that the phosphatidylinositol-3-kinase (PI3K)/Akt pathway is altered after ischaemia/reperfusion injury in the diabetic myocardium. We hypothesized that DM-induced cardiac dysfunction in donors is further impaired after heart transplantation and that PI3K/Akt-pathway alterations may be one of the underlying pathomechanisms.
Gesehen am 22.01.2020